INTEGRASI KEUANGAN HIJAU: MENGUJI DAMPAK GREEN ACCOUNTING, KINERJA LINGKUNGAN, DAN CSR TERHADAP PROFITABILITAS PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2021–2023) - Yosi Stefhani; Dintan Anisa; Noviarti (Pasca Sarjana Universitas Satya Negara Indonesia, 2026)
Abstract In the modern business landscape, energy sector companies face intense pressure to balance financial performance with environmental responsibility. This study examines the effect of green accounting, environmental performance, and corporate social responsibility (CSR) on profitability. Using a quantitative approach, the data were collected from annual reports and sustainability reports available on the Indonesia Stock Exchange (IDX) as well as the companies’ official websites. Through purposive sampling, 11 energy sector companies listed on the IDX were selected over a three-year period (2021–2023), yielding 33 firm-year observations. Data were analyzed trough classical assumption testing and multiple linear regression analysis using Jamovi statistical software. The simultaneous regression results indicate that green accounting, environmental performance, and corporate social responsibility collectively affect corporate profitability. Partially, the findings reveal that green accounting has a significant impact on profitability, whereas environmental performance and corporate social responsibility do not exhibit a significant effect. These insights underscore the varying strategic impacts of sustainability initiatives on the financial outcomes of energy enterprises.